2021
DOI: 10.1021/acs.biomac.1c01186
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbranched Polyesters Based on Indole- and Lignin-Derived Monomeric Aromatic Aldehydes as Effective Nonionic Antimicrobial Coatings with Excellent Biocompatibility

Abstract: This research aims to investigate nonionic hyperbranched polyesters (HBPs) derived from indole and lignin resources as new nontoxic antimicrobial coatings. Three nonionic HBPs with zero to two methoxy ether substituents on each benzene ring in the polymer backbones were synthesized by melt-polycondensation of three corresponding AB 2 monomers. The molecular structures and thermal properties of the obtained HBPs were characterized by gel permeation chromatography, nuclear magnetic resonan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 73 publications
(169 reference statements)
0
14
0
Order By: Relevance
“…This suggested that the substitutions with alky (either linear or cyclic) groups on indole NH could decrease the hemocompatibility of the resulting polymers to some extent, while the substitutions with ether groups have no significant impact on the hemocompatibility, which is consistent with other reported polymers with ether groups. 90,91…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggested that the substitutions with alky (either linear or cyclic) groups on indole NH could decrease the hemocompatibility of the resulting polymers to some extent, while the substitutions with ether groups have no significant impact on the hemocompatibility, which is consistent with other reported polymers with ether groups. 90,91…”
Section: Resultsmentioning
confidence: 99%
“…(either linear or cyclic) groups on indole NH could decrease the hemocompatibility of the resulting polymers to some extent, while the substitutions with ether groups have no significant impact on the hemocompatibility, which is consistent with other reported polymers with ether groups. 90,91 Conclusions A new series of nonionic indole-based biodegradable poly (vinyl alcohol)s with different N-substituents were synthesized, which showed tuneable glass transition temperatures (39-93 °C) and desirable thermal stability. According to the disk diffusion assay, all these polymers showed effective antibacterial function against 9 different human pathogens.…”
Section: Papermentioning
confidence: 99%
“…After 48 h of treatment, we studied the toxicity of the polymers using a 3-(4,5dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. 35 Protein purification G-actin was extracted from rabbit skeletal muscle acetone powder. 36 Actin was labeled with N-(1-pyrene) iodoacetamide (P-29, Molecular Probes).…”
Section: Cellular Experimentsmentioning
confidence: 99%
“…This could suggest that the ether or alkyl groups of phenolic HBPs could enhance their molecular interaction with the membrane of certain G(À) bacteria, which presumably could be related to their enhanced structural hydrophobicity. 64,95…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…by spin coating). 64 To our knowledge, the potential of dendritic polymers with phenol termini as new antimicrobial materials have not been investigated.…”
Section: Introductionmentioning
confidence: 99%